KARIFAN LOKAL MASYARAKAT BUTON (PARIKA) DALAM USAHATANI PADI LADANG DI DESA KAMPUNG BARU KECAMATAN KULISUSU UTARA KABUPATEN BUTON UTARA - Erdin Erdin; La Nalefo; Mardin Mardin (Universitas Halu Oleo, 2023)
Field rice plants are a favorite source of food for the people of Buton Utara Regency, especially before the celebration of religious holidays and harvest festivals. The purpose of this study was to determine the role of parika in the process of cultivating upland rice and the form of local wisdom in the process of cultivating upland rice to meet their daily needs. The data used in this study are primary data and secondary data and using a qualitative descriptive analysis. The results of the study show that the role of parika in the process of cultivating field rice plants is very large, starting from the process of land preparation, planting, maintenance, harvesting, and post-harvest which is in charge of guiding every activity. The form of community local wisdom in cultivating field rice plants in Kampung Baru Village is matantasu which means the midpoint of planting and can be seen in real terms in the planting process.